Investigation of formaldehyde and TVOC in underground malls in Xi'an, China: Concentrations, sources, and affecting factors. (February 2015) - Tao, Haitao; Fan, Yuesheng; Li, Xiaoqing; Zhang, Ziran; Hou, Wensheng
Abstract: Along with the speeding up of Chinese urbanization process, the contradiction between urban land demand and supply had increased significantly, more and more underground structures appeared, and were used as crowed shopping malls, etc. However, concentrations of formaldehyde and total volatile organic compounds (TVOC) in underground malls were higher than that of outdoors. In this study, concentration levels of formaldehyde and TVOC were investigated from 9 underground malls in Xi'an, China. Simultaneously, the sources and affecting factors were discussed. Results showed that the mass concentrations of formaldehyde and TVOC in underground malls exceeded the allowed figures and the over-standard rate reached 66.7% and 77.8%, respectively. The mean mass concentrations of formaldehyde and TVOC in all 9 underground malls ranged from 0.05 mg/m 3 to 0.26 mg/m 3 and from 0.34 mg/m 3 to 3.56 mg/m 3, respectively. The concentrations of formaldehyde and TVOC pollution were more serious in oversize underground malls than those in small ones. The main pollution sources of formaldehyde and TVOC in underground malls were interior decoration materials and merchandises sold, which illustrated that the lack of ventilation volume in the underground malls. Further analysis indicated that a strong negative correlation existed between formaldehyde and TVOC concentrations and indoor air velocity, while those significant positive correlations existed between formaldehyde and TVOC concentrations and indoor temperature and indoor relative humidity, respectively. Correlations noted that increased indoor ventilation rates or reduced the indoor temperature and indoor relative humidity appeared to decrease the indoor concentrations of formaldehyde and TVOC. Highlights: An investigation of the formaldehyde and TVOC concentrations in underground malls of China. Experimental results included concentrations, sources, and affecting factors. Correlations between concentrations and affecting factors were studied.